2012
DOI: 10.1097/nor.0b013e3182558d0b
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Multimodal Pain Management Protocol in Total Knee Arthroplasty Patients

Abstract: The multimodal pain approach improved patient outcomes in TKA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
1
8
2
Order By: Relevance
“…This is the fi rst study to evaluate the PCA knowledge of elderly patients. The highest postoperative pain scores recorded in the early postoperative period were less than 7 for the vast majority of patients, indicating that their perceived pain level was not too severe, contrary to prior reports about pain for joint replacement surgery ( Dalury et al, 2012 ;Lewis et al, 2012 ;Meftah et al, 2012 ). Our observation of low postoperative pain scores may be related to recent changes in total knee replacement analgesic standards, which include the use of regional femoral nerve blocks for the fi rst 24-36 hours postoperatively in total knee replacement surgeries.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…This is the fi rst study to evaluate the PCA knowledge of elderly patients. The highest postoperative pain scores recorded in the early postoperative period were less than 7 for the vast majority of patients, indicating that their perceived pain level was not too severe, contrary to prior reports about pain for joint replacement surgery ( Dalury et al, 2012 ;Lewis et al, 2012 ;Meftah et al, 2012 ). Our observation of low postoperative pain scores may be related to recent changes in total knee replacement analgesic standards, which include the use of regional femoral nerve blocks for the fi rst 24-36 hours postoperatively in total knee replacement surgeries.…”
Section: Discussioncontrasting
confidence: 83%
“…Our observation of low postoperative pain scores may be related to recent changes in total knee replacement analgesic standards, which include the use of regional femoral nerve blocks for the fi rst 24-36 hours postoperatively in total knee replacement surgeries. Prior studies that reported on postoperative pain levels during the fi rst postoperative day in joint replacement patients either had no or few patients with femoral blocks, different from the majority of patients in our study ( Dalury et al, 2012 ;Lewis et al, 2012 ;Meftah et al, 2012 ).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…[5][6][7] Improvements in pain management following TKA have been associated with early ambulation, thereby lowering the risk of postoperative complications and reducing length of stay. 8 The advent of fast-track surgery programs in North America and Europe may reduce length of stay by identifying and addressing factors that cause patients to remain in hospital. 9 One of these factors is pain, so discharge after TKA may be accelerated by effective postoperative pain management.…”
Section: Introductionmentioning
confidence: 99%
“…From April 1, 2010, to March 31, 2011, there were 47,113 acute-care hospitalizations for primary TKA in Canada, of which 6,392 were in British Columbia. 1 Immediate consequences after TKA include significant pain, 2 swelling, 3 limited movement, 4 nausea or vomiting, 5 and potential blood loss. 6 The goal of surgery is to reduce pain, improve function, and maximize knee range of motion (ROM).…”
mentioning
confidence: 99%